Illuminating Hidden Harvests The contributions of small-scale fisheries to food security and nutrition - Mills, David; Simmance, Fiona; Byrd, Kendra; Robinson, James; Garrido-Gamarro, Esther; Pincus, Lauren; Ahern, Molly; Cohen, Philippa; Fiorella, Kathryn; Hicks, Christina; Kjellevold, Marian; Roscher, Matthew; et al. (FAO, 2023)
This chapter leverages these new data and innovative predictive models to illuminate the global, regional and national nutritional contributions from small-scale fisheries. Where data do not yet support large-scale synthesis, a focus on certain data “bright spots” provides examples of how analysis of quality data can highlight entry points and policy directions. These illustrate where and how data and research can change to better understand the contributions of small-scale fisheries to food security and nutrition. Modifications to existing demographic, agricultural or fisheries survey systems that account for the idiosyncrasies of small-scale fisheries can substantially improve the quality and relevance of data for improved fisheries management.